A Case Study of the Hashtag #Freepalestine: Cultural Communication and Public Opinion Transformation - Anisa, Nurul; Harjoko, Ivone; Khadifa, Rachmad (Ilomata International Journal of Social Science, 2023)
This study involves an in-depth analysis of Cultural Communication and Public Opinion Transformation through a case study of the hashtag #FreePalestine on social media. The Israeli-Palestinian controversy sparked a significant shift in public opinion, and these hashtags became an important instrument in weaving complex online narratives. This research aims to understand the impact of Cultural Communication through the hashtag #FreePalestine in transforming public opinion. Her focus includes online mobilization, influence on policy, changing international perceptions, and the formation of activist movements. This research method uses a mixed approach, namely combining qualitative and quantitative analysis. Data collection was carried out on 6 – 25 December 2023. Social media analysis was carried out to track trends, sentiment and relationship networks, while interviews and surveys were used to gain a deeper understanding of the influence of opinion transformation in the real world. This research shows that the hashtag #FreePalestine not only creates changes in online opinion but also mobilizes real action and shapes global narratives that influence policy and business. Cultural communication on social media is key to understanding further impact, with image visualization and visual solidarity being key elements in changing public opinion. The real-world implication of these findings is the importance of understanding the role of social media in shaping public perceptions and opinions regarding global conflict. In the future, this can serve as a guide for policy makers, activists and researchers to design more effective communication strategies in addressing sensitive issues such as the Israeli-Palestinian conflict.